Kebijakan Food Security : Arah Kebijakan dan Strategi Ketahanan Pangan Pemerintah Indonesia - Nudia Indah P.; Aprilia Setyaningsih (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Food is the initial priority need of humans as living things. While food security is defined as meeting the needs continuously. Because food security is a guarantee for living things to work productively. This paper aims to examine: 1. The direction of policy, and 2. food security strategies. This paper is carried out from various literature studies from the results of research related to the aspects of the discussion. The results show that 1. The direction of food security policy so far certainly wants to realize food independence from the household to the national level and 2. Indonesia's food security strategy is expected to be able to compete in the future so that an active and responsive government with food security is needed.